Bromination of 2,S-dimethoxybenzaldehyde - Ahmad, Faujan; Bruce, Malcolm J. (1984)
Bromination of 2,5-dimethoxybenzaldehyde (1) gives 4-bromo-2,5-dimethoxy-benzaldehyde (2) and not 6-bromo-2,5-dimethoxybenzaldehyde (3) as previously reported by Rubenstein (1925). It appears that the conjugation of the carbonyl group with the ortho methoxy group (as structure 4) does not control the orientation of this bromination reaction. A series of reactions which confirm the structure of the bromination product will be discussed.